Analysis of forest fire dangers of the Bryansk region in the zones of radioactive contamination and beyond - A. I. Radin; T. A. Marchenko; A. N. Razdaivodin (Радиационная гигиена)
The purpose of the study is to analyze the forest fire dangers of the Bryansk region forests, taking into account their radioactive contamination and potential risks for forestry workers involved in forest fires extinguishing. Significant areas of radioactive contamination of forests with a predominance of sites belonging to the classes of high and very high natural fire danger, restrictions on economic activity and a long fire-hazardous period contribute to the occurrence of radioactive forest fires. The analysis of the combined data on forest fires and radioactive contamination of forest areas showed that most forest fires occur outside the zones of radioactive contamination and are not radioactive. The largest number of fires occurs at the beginning of the fire season. Radioactive forest fires in most cases arise from the burning of dry grassy vegetation, as a result of the transition from lands of other categories and through the fault of the population. The average effective dose of additional radiation per a workday can be estimated at 1.96 μSv, and the maximum at ~ 15.4 μSv. Most fires are extinguished in the early stages and do not have time to cover large areas. It indicates the effective work of the forest fire service